Unique short-circuit failure mechanisms in 1.2-kV SiC planar MOSFETs - Kazuhiro Suzuki; Kaito Kashimura; Hiroshi Yano; Noriyuki Iwamuro (Applied Physics Express)
This study clarified a unique failure mechanism in 1.2-kV SiC planar MOSFETs during short-circuit transients at 400-V DC bias in which molten Si penetrated cracks in the gate interlayer dielectric that were generated by mechanical stress, resulting in the shorting of the gate-source electrodes. In addition, the study found that the molten Si came from the poly-Si gate during the short-circuit transients. Since the latest planar SiC MOSFETs have superior specific on-resistances, the peak drain current density during short-circuit transients is higher, so greater heat generation occurs, resulting in the poly-Si gate reaching its melting point.